2022
DOI: 10.1016/j.dcn.2022.101072
|View full text |Cite
|
Sign up to set email alerts
|

A tutorial on the use of temporal principal component analysis in developmental ERP research – Opportunities and challenges

Abstract: Developmental researchers are often interested in event-related potentials (ERPs). Data-analytic approaches based on the observed ERP suffer from major problems such as arbitrary definition of analysis time windows and regions of interest and the observed ERP being a mixture of latent underlying components. Temporal principal component analysis (PCA) can reduce these problems. However, its application in developmental research comes with the unique challenge that the component structure differs between age gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 146 publications
1
22
0
Order By: Relevance
“…Recorded EEG channels are usually noisy. Techniques such as principal component analysis (PCA) [34], [35] and independent component analysis (ICA) [36], [37] are often used to remove noise and extract the ERP signals. In this work, we used CorrCA to nd the components having maximal correlation across the target trials cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recorded EEG channels are usually noisy. Techniques such as principal component analysis (PCA) [34], [35] and independent component analysis (ICA) [36], [37] are often used to remove noise and extract the ERP signals. In this work, we used CorrCA to nd the components having maximal correlation across the target trials cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the identification of ERP components in the measured ERPs is obscured because the measured ERPs are a mixture of latent underlying (sub-) components. Spatial and temporal overlap considerably biases the observed component peaks typically used to identify and label components ( Scharf et al, 2022 ). Moreover, the practice of determining time windows for the respective components based on (peaks in) the observed ERP frequently suffers from the relatively arbitrary definition of time windows and double dipping ( Kriegeskorte et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the practice of determining time windows for the respective components based on (peaks in) the observed ERP frequently suffers from the relatively arbitrary definition of time windows and double dipping ( Kriegeskorte et al, 2009 ). Temporal PCA largely reduces these problems (e.g., Dien, 2012 ; Scharf et al, 2022 ). For that reason, we used temporal PCA to delineate the components in a straight-forward, data driven approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the volume conduction, ERP components overlap in temporal and spatial domain to some extent. Thus, the factors are required to be correlated substantially (Dien, 1998;Scharf et al, 2022). Besides, the results of actual and stimulated ERP datasets indicated that Promax rotation showed more accurate results than Varimax rotation (Dien et al, 2005;Dien, 1998;Dien et al, 2003).…”
Section: Procedures For Pca Applicationmentioning
confidence: 99%